Unique Structures, Properties and Applications of Dendrimers - Gupta, Ankita; Dubey, Shaifali; Mishra, Mayuri (Journal of Drug Delivery and Therapeutics, 2018)
Dendrimers are novel three dimensional, hyperbranched globular nano polymeric architectures. Attractive features like nanoscopic size, narrow polydispersity index and excellent control over molecular structure afford dendrimers with ideal drug delivery ability through encapsulating drugs in their interior or covalently conjugating drugs on their surfaces. The adaptable surface functionalization ability enables covalent conjugation of various targeting molecules onto the surface of dendrimers, thereby allowing for generation of various multifunctional nanodevices for targeted drug delivery applications. Drug delivery researchers are especially enthusiastic about possible utility of dendrimers as drug delivery tool. However, to get the maximum benefits of these novel class macromolecules, a research by collaboration is very much essential. Finally, it is one of the youngest and exciting fields of polymer researches where all branches of science can take part and hence, deserves more intensive attention. Keywords: Dendrimers, Drug Delivery, Targeting, Dual Drug Loading, PAMAM